A polyhedral metal–organic framework based on the supermolecular building block strategy exhibiting high performance for carbon dioxide capture and separation of light hydrocarbons. Issue 83 (4th September 2015) - Wang, Dongmei; Liu, Bing; Yao, Shuo; Wang, Tao; Li, Guanghua; Huo, Qisheng; Liu, Yunling
Abstract : A PMOF was assembled by the SBB strategy, which exhibited high performance for CO2 capture and separation towards CO2, C2 H6 and C3 H8 over CH4 . Abstract : By using the supermolecular building block (SBB) strategy, a polyhedron-based metal–organic framework (PMOF), which features three types of cages with multiple sizes and shapes, has been synthesized. It exhibits high performance for CO2 capture (170 cm 3 g −1 at 273 K under 1 bar) and selectivity of CO2 /CH4 (9.4) and C3 H8 /CH4 (271.5).